PERUBAHAN IKLIM DAN KASUS MALARIA: PEMAHAMAN DAN PERILAKU KESEHATAN MASYARAKAT DI KABUPATEN KEBUMEN - Augustina Situmorang; Widayatun Widayatun; Zainal Fatoni; Yuly Astuti; Sari Seftiani (Jurnal Masyarakat dan Budaya, 2012)
Previous studies indicate that the complexity of malaria transmission in certain areas is influenced by the indirect impact of climate change as well as non-climate factors, such as population mobility, behaviour and their access to health services. This paper aims to discuss the knowledge, understanding and health behaviour of rural community related to malaria and climate change. Information presented in this paper is mainly based on field research conducted in Kebumen District in 2010, and supported by a desk review of secondary data, related documents and previous studies. The study shows that several areas (village or sub-district) in Kebumen are vulnerable to malaria. Trend of malaria tends to increase during the last three years (2008-2010), meanwhile malaria outbreaks occur almost every year in different places. Even though local people are aware of the weather and temperature changes in their areas, they have not linked it with climate change phenomenon. People’s knowledge of malaria in terms of the source of the disease, the tranmission of malaria and the various method of malaria prevention is relatively limited and has not been practiced in their daily life. Therefore, an active participation of the government, the private sector and the local community is needed to address this situation. Keywords: malaria, climate change, knowledge and behaviour, rural community, Kebumen district